Pulsed electric field: A “green” extraction technology for biomolecular products from glycerol with fermentation of non-Saccharomyces yeasts - Tsapou, Evangelia A.; Ntourtoglou, George; Drosou, Fotini; Tataridis, Panagiotis; Lalas, Stavros; Dourtoglou, Vassilis (Frontiers in Bioengineering and Biotechnology, 2022)
Glycerol is the main organic by-product of the biodiesel industry and it can be a source of carbon for fermentations or a substrate for biotransformations. This work investigates a process that uses pulsed electric field (PEF) to enhance polyol and propanediols extraction from a glycerol/glucose fermentation broth. Three different commercial, non-Saccharomyces strains, Torulaspora delbrueckii Prelude (Hansen), Torulaspora delbrueckii Biodiva 291 (Lallemand) and Metschnikowia pulcherrima (Lallemand) were studied. The results revealed that PEF had a positive impact on the extraction of polyols ranging from 12% to 191%, independently of fermentation conditions. Torulaspora delbrueckii Biodiva 291 (Lallemand) was found to be more efficient at pH 7.1. An optimized chromatography-based method for the qualitative and quantitative determination of the formed products evaluated. The experiments were carried out either in flasks or in a bioreactor.